Performance of General Bureau Civil Servants in The Regional Secretariat of North Sulawesi Province - Astron, Edwin; Kandouw, Selpius; Mamonto, Fitri H. (Technium Social Sciences Journal, 2024)
The aim of this research is to describe, interpret and analyze the performance of Civil Servants (PNS) in the Administration Sub-Section for Leadership and Expert Staff of the General Bureau of the Regional Secretariat of North Sulawesi Province seen from the aspects of Employee Performance Targets (SKP), Discipline and the application of Civil Service principles State (ASN) "BerAKHLAK" (Service Oriented, Responsible, Competent, Harmonious, Loyal, Adaptive and Collaborative). The research method applied is a descriptive qualitative approach using observation, interview, and document analysis techniques. The research results revealed a performance gap among civil servants, where some succeeded in achieving satisfactory results while others did not meet expectations. Factors such as effective training, motivation, conducive work environment, and reward and punishment systems were identified as important determinants in achieving optimal performance. The obstacles faced involve the quality and quantity of Human Resources (HR), with uncertainty that all civil servant members can contribute collectively. Therefore, a more thorough and objective performance measurement approach is needed. This research suggests an increase in the implementation of intensive training, improvements in the motivation system through structured rewards, evaluation of work environment conditions, as well as collaborative efforts with external parties to enrich technological understanding and skills.